2020
DOI: 10.1101/2020.05.24.20111724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19: Impact of Obesity and Diabetes in Disease Severity

Abstract: Background: The Coronavirus disease 2019 (COVID19) pandemic is straining the healthcare system, particularly for patients with severe outcomes who require admittance to the intensive care unit (ICU). This study aimed to investigate the potential associations of obesity and diabetes with COVID19 severe outcomes, assessed as ICU admittance. Subjects: Demographic and patient characteristics from a retrospective cohort of 1158 patients hospitalized with COVID19 in a single center in Kuwait, along with their medica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…A total of six studies[ 21 , 23 , 24 , 25 , 28 , 29 ] were included in the dose-response meta-analysis of the association between BMI and critical COVID-19. It was found that there was a linear relationship (P non-linearity = 0.242) between BMI and the risk of critical COVID-19 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of six studies[ 21 , 23 , 24 , 25 , 28 , 29 ] were included in the dose-response meta-analysis of the association between BMI and critical COVID-19. It was found that there was a linear relationship (P non-linearity = 0.242) between BMI and the risk of critical COVID-19 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another Mexican study with 51,633 patients showed similar results, with a significant increased lethality rate in patients with obesity (HR: 1.25 (1.17–1.34, p < 0.001) [ 27 ]. These reports with large patient cohorts are further strengthened by multiple clinical studies with smaller collectives worldwide [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Interestingly, Lighter et al and Ebinger et al showed that middle aged patients with an age below 52 and up to 60 years were more affected by obesity (BMI 30–34 and ≥35) with an HR: 2.0 (1.6–2.6, p < 0.0001)) and HR: 2.2 (1.7–2.9, p < 0.0001), respectively, resulting in increased morbidity rates compared to >60 years old patients [ 31 , 43 ].…”
Section: Clinical Correlation Of Covid-19 With Obesitymentioning
confidence: 91%
“…An audit of 124 patients admitted to ICU in France observed that among patients with COVID-19, obesity (BMI >30-<35 kg/m 2 ) and severe obesity (BMI >35 kg/m 2 ) were more prevalent than in control patients admitted to ICU for other causes: 47.6 vs. 25.2% and 28.2 vs. 10.8%, respectively, and those requiring invasive mechanical ventilation were also more obese (24). In a multivariate analysis of hospitalized patients in Kuwait, the risk of requirement for ICU was increased in the obese OR 2.7 (CI 1.17, 6.20) and those with morbid obesity (BMI >40) OR 3.95 (CI 1.0-15.2) (19). A similar study from New York that included 1,331 hospitalized COVID-19 patients, of whom 431 were admitted to ICU, found that the association with obesity was only evident in younger patients <60 years old with a higher risk of ICU admission for those with obesity (OR 1.8, CI 1.2, 2.7) and severe obesity (OR 3.6, CI 2.5, 5.3) compared to patients with a BMI <30 (25).…”
Section: Obesity Diabetes Effects On Covid-19 Risk and Severitymentioning
confidence: 96%